Electrical discharge machining of polycrystalline diamond using copper electrode – finishing condition - Ahmad, M.A. Haikal; Rahim, M. Zulafif; Mohd Fauzi, M. F.; Azis, N. Hafizah; Ismail, A.E.; Hassan, Mohd Fahrul; Arifin, A.M.T.; Yusof, M.S.; Ibrahim, M. Rasidi (IOP Publishing, 2017)
Research on machining process of Polycrystalline Diamond (PCD) is becoming important as the material was believed suitable to be used for cutting tools of advanced aeronautical structure. Electrical Discharge Machining (EDM) was regarded as the suitable method to machine PCD due its noncontact process nature. The objective of this research is to determine the influence of several EDM parameter such as sparking current, pulse duration, and pulse interval to the material removal rate and surface roughness of the machined PCD. Instead of significantly influenced the material removal rate, the sparking current was also highly influenced tha surface roughness. Highest material removal rate of approximately 0.005mm3/s was recorded by the EDM process with the highest current used of 5A, and lowest pulse interval of 1µs. The influence of pulse duration is not clearly seen at the lowest pulse interval used. On the other hand, 0.4µm was the lowest surface roughness value obtained in this research indicated by the highest sparking current, highest sparking duration and lowest sparking interval of 5A, 1µs and 1µs respectively.